2020
DOI: 10.5056/jnm20012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Patient With Symptoms of Colonic or Anorectal Motility Disorders

Abstract: Constipation, irritable bowel syndrome, fecal incontinence, abdominal pain, and anorectal pain are problems that affect 40% of the population. They commonly present with overlapping symptoms indicating that their pathophysiology affects multiple segments of the gut as well as brain and gut interactions. Clinically, although some conditions are readily recognized, dyssynergic defecation, fecal incontinence, and anorectal pain are often missed or misdiagnosed. Consequently, the assessment of lower gastrointestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…A recent multi-national, survey-based study showed that among 73.076 adults, more than 30% met the criteria for having at least one functional bowel disorder, e.g. irritable bowel syndrome, functional constipation or slow transit constipation [ 1 , 2 ]. Such disorders, in which intestinal motility is abnormal, are often accompanied by difficulty with defecation, abdominal pain and may drastically decrease the quality of life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent multi-national, survey-based study showed that among 73.076 adults, more than 30% met the criteria for having at least one functional bowel disorder, e.g. irritable bowel syndrome, functional constipation or slow transit constipation [ 1 , 2 ]. Such disorders, in which intestinal motility is abnormal, are often accompanied by difficulty with defecation, abdominal pain and may drastically decrease the quality of life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…irritable bowel syndrome, functional constipation or slow transit constipation [ 1 , 2 ]. Such disorders, in which intestinal motility is abnormal, are often accompanied by difficulty with defecation, abdominal pain and may drastically decrease the quality of life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess bowel symptoms in the context of LARS, a real‐life prospective stool diary could be considered as a reference method, since it records every bowel movement and stool leakage as it occurs in detail [ 7 , 8 ]. However, a 7‐day stool diary is time‐consuming for the patient and labour‐intensive for the clinician to analyse in depth.…”
Section: Introductionmentioning
confidence: 99%
“…15% in North America) and seriously affect the quality of life with significant socio-economic costs [1]. The health care pathway of these patients remains complex as the symptoms do not permit the physician to identify the pathophysiological origins of those trouble even with in-depth clinical investigations [2].…”
Section: Introductionmentioning
confidence: 99%